Using night shift worker and employee health stakeholder perspectives to inform the development of Arcashifttm, a digital precision circadian medicine intervention for shift work disorder - Paige Coyne; Matthew B. Jennings; Sara Santarossa; Dana Murphy; Maya Zreik; Helena Bryans; Christopher Drake; Olivia Walch; Philip Cheng (BMC Digital Health)
Abstract Background More than a quarter of night shift workers (NSWs) have symptoms severe enough to meet diagnostic criteria for Shift Work Disorder (SWD). This study sought to understand the experiences of both NSWs and employee health stakeholders (EHSs) to inform the design of an effective digital precision circadian medicine intervention for NSWs experiencing SWD. Methods NSWs (N = 20) participated in virtual focus groups (N = 5) and were asked about their experiences with night shift work, desired components of a digital intervention for SWD, and feedback on a potential digital precision circadian medicine intervention (i.e., Arcashift™) for SWD. Eligibility criteria: fixed night schedule for 6 + months, diagnosed with SWD, and aged 18–50 years. EHSs (N = 5) participated in virtual 1-on1 interviews, where they were asked about what motivations, goals, and return-on-investments (ROIs) mattered with regards to investing in a digital intervention for NSWs. Focus groups and interviews were digitally recorded and transcribed. Combined transcript reflexive thematic analysis was conducted to identify themes. Results The reflexive thematic analysis produced three themes. The first theme, the trials and tribulations of night shift work, related to the physical, mental, and emotional tolls related to working the night shift and resulted from problem-focused discussions with NSWs about what it is like to work the night shift. Subthemes included: physically and mentally draining, the world runs on daytime hours, and lack of respect and consideration. The remaining two themes, thrown to the wolves and shifting towards an app, were the result of shifting focus group conversations with NSWs and interviews with EHSs towards solution-focused thinking by presenting a digital precision circadian medicine intervention (i.e., Arcashift™) through which NSWs’ SWD could be improved. Conclusion This study represents a strong preliminary step toward the development of an app for the intervention of SWD. There is a critical need for a real-world intervention for SWD, and stakeholders were optimistic about the potential of an app to help address SWD. Future work is needed to assess the extent to which the proposed app, informed by these stakeholder insights, is able to improve outcomes for employees and ROIs for EHSs.